Prospects and utilization of tropical plantation trees - Liew, Kang Chiang, 1973- (Boca Raton, FL : CRC Press, 2020)
"This book focuses on utilization of tropical plantation trees of Malaysia with attention to the aspects of economics and business, planting and managing, and products of the trees"--
OCLC-licensed vendor bibliographic record.
Keywords: Tree farms -- Malaysia; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General